Piece=part=portion : fractions=decimals=percents - Gifford, Scott, 1955-; Thaler, Shmuel (Berkeley, CA : Tricycle Press, 2003)
Explains how in the language of mathematics, fractions, decimals, and percents are three different ways of describing the same parts of things.
Horn Book.
Kirkus Review.
School Library Journal.
1.2
6.2.
3-6
Keywords: Fractions -- Juvenile literature; Logic, Symbolic and mathematical -- Juvenile literature; Decimal fractions; Fractions; Percentage; Decimal system; Fractions; Percentage